2009
DOI: 10.1016/j.neulet.2009.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Observing shadow motions: Resonant activity within the observer's motor system?

Abstract: a b s t r a c tSeveral studies have demonstrated that the human motor cortex is activated by the mere observation of actions performed by others. In the present study, we explored whether the perception of 'impoverished motion stimuli', such as shadow animations, is sufficient to activate motor areas. To do so, transcranial magnetic stimulation (TMS) was applied over the hand area of the primary motor cortex (M1) while subjects observed shadow animations depicting finger motions. Data showed that resonant moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 19 publications
5
21
1
Order By: Relevance
“…Particularly for experiment 2, we demonstrated a general significant facilitation of corticospinal excitability during movement observation, i.e. MEPs elicited during grasp observation were larger than during baseline measurements which is in line with previous studies Alaerts, Van Aggelpoel, Swinnen, & Wenderoth, 2009;Fadiga, Fogassi, Pavesi, & Rizzolatti, 1995 Lemon, 2009;Sartori, Betti, & Castiello, 2013). Accordingly, the general MEP facilitation is more pronounced for FDI than for ADM (as found in Exp.…”
Section: General Versus Grip Specific Changes Of Corticomotor Excitabsupporting
confidence: 92%
“…Particularly for experiment 2, we demonstrated a general significant facilitation of corticospinal excitability during movement observation, i.e. MEPs elicited during grasp observation were larger than during baseline measurements which is in line with previous studies Alaerts, Van Aggelpoel, Swinnen, & Wenderoth, 2009;Fadiga, Fogassi, Pavesi, & Rizzolatti, 1995 Lemon, 2009;Sartori, Betti, & Castiello, 2013). Accordingly, the general MEP facilitation is more pronounced for FDI than for ADM (as found in Exp.…”
Section: General Versus Grip Specific Changes Of Corticomotor Excitabsupporting
confidence: 92%
“…First, results based on EEG signals do not reflect similar aspects of cortical activity obtained by other techniques, such as fMRI and TMS. For example, it is difficult to discuss the results of the present study in the same context as findings reported in Alaerts et al [76] since the techniques used, the areas investigated, and the motions observed, all differ: EEG vs TMS, all scalp areas vs primary motor cortex, whole body motions vs hand motions. Second, attention should also be paid to the experimental design.…”
Section: Discussionmentioning
confidence: 44%
“…Wildschut (2010) found that dance spectators who sit further away are less emotionally and kinaesthetically absorbed in the movements they observe. However, the motor system is involved in mirroring observed actions even when the body is only sparsely (Alaerts, Van Aggelpoel, Swinnen, & Wenderoth, 2009) or not at all visible, as in point-light displays (see Jola et al, 2011). Also, the distance between spectators and stage was consistent throughout out the experiment, and thus cannot explain the changes we found in MEPs during action observation.…”
Section: Null-findingsmentioning
confidence: 75%